Implementasi E-Government pada Aplikasi Pds-Pajak Daerah Kabupaten Sidoarjo: (Studi Kasus di Badan Pelayanan Pajak Daerah Kabupaten Sidoarjo) - Diana Balqis; Imelda Dian Rahmawati (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Implementation of E-Government can improve the quality of public services through the use of information and communication technology in the government administration process. The Sidoarjo Regency Tax Services Agency also takes advantage of technological developments by issuing the Sidoarjo Regional PDS-Tax Application. The PDS Application System has been implemented at BPPD to improve services in tax activities. The success of implementation can be seen from the positive response given by Taxpayers. Although there are still obstacles faced in implementing the PDS application, such as not everyone being technologically literate. These obstacles are not a serious problem, because BPPD Sidoarjo Regency carries out outreach at all times, both directly and indirectly. The theory used is the theory of policy implementation put forward by Merilee S. Grindle. The method used is a descriptive research method with a qualitative approach. The data collection technique is through field studies consisting of observation, interviews and documentation. The results of the research show that the implementation of the PDS Application Policy is going well, this is made clear by the implementation being right on target, the socialization carried out is going well as seen from Taxpayers who already know and use the PDS Application in carrying out tax activities.